PENGARUH LOKASI, FASILITAS DAN HARGA TERHADAP MINAT BELI PERUMAHAN GRAND GRESIK HARMONI DESA SREMBI – KEMBANGAN KECAMATAN KEBOMAS GRESIK - Elisya Nurita Pertiwi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to test the effect of location, facilities and prices on consumer buying interest in the Gr and Gresik Harmoni Housing in Srembi Kembangan Village, Kebomas Subdistrict, Gresik. Then a literature review and hypotheses were compiled, as well as data obtained from questionnaires on 70 Gresik people who had visited the Grand Gresik Harmoni housing using nonprobability sampling techniques. Tests are carried out using instrument tests, testing classical assumptions and also multiple linearity. The results of the analysis obtained results Y = 0.204 + 0.369X1 + 0.653X2 + 0.226X3 + e so that it can be concluded that the location affects partial buying interest, the facility affects partial buying interest, and prices also influence partial buying interest.